Relational Meir-Keeler Contractions and Common Fixed Point Theorems. (25th June 2022) - Khan, Faizan Ahmad; Sk, Faruk; Alshehri, Maryam Gharamah; Khan, Qamrul Haq; Alam, Aftab
Abstract : In this article, we prove some coincidence and common fixed point theorems under the relation-theoretic Meir-Keeler contractions in a metric space endowed with a locally finitely T -transitive binary relation. Our newly proved results generalize, extend, and sharpen some existing coincidence point as well as fixed point theorems existing in the literature. Moreover, we give some examples to affirm the efficacy of our results.